Reducing ground borne noise due to railways: A practical application. (July 2021) - Jean, Philippe; Guigou-Carter, Catherine
Abstract: The construction of new buildings very close to existing tracks, with heavy commuting traffic, requires careful design. Such projects must be accompanied with noise and vibration reduction measures. The practical case here considered has been analysed by first assessing the existing situation prior to construction (type of soil and traffic). In a second stage, we have proposed and quantified solutions to reduce vibration and ground-borne noise levels inside the buildings. A 2.5D FEM/BEM commercial software (Mefissto), developed by CSTB, has been employed in what is a very challenging numerical context: multi-layered ground, large multi-levels buildings, large frequency range (10–250 Hz). In every situation, the use of an original 2.75D approach leads to the low frequency noise levels inside the buildings. As the trackwork cannot, in this case, be modified the solutions tested consist in inserting different types of barriers in the ground or in inserting either spring of resilient bearings (decoupling) in the lower part of the structure. Results are compared to target values in terms of vibration and ground-borne noise levels selected in order to limit dwellings occupants' annoyance. Satisfactory results can only be achieved with the use of the decoupling solution.